IMF Staff papers : Volume 20 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1973)
It is argued in this paper that, since economic welfare is influenced by the payments objectives pursued by countries, economists should explore the objectives that are indicated as being appropriate by welfare economics, rather than accepting objectives that have been arbitrarily specified and restricting their analysis to the question of how those objectives can be achieved. The concept of payments objectives involves targets for both the change in reserves and the structure of the balance of payments. The paper assumes that the private sector supplies the optimal quantity of stabilizing speculation, so that there is no need for reserves to change, and the problem is solely that of determining the optimal capital flow. This permits a discussion of the sources of welfare gain from capital flows, the qualifications to the classical prescription of free capital flows, and the case for a code of conduct to limit countries' freedom to restrict capital movements. It also implies that in the long run any maldistribution of reserves should be corrected by adjusting the current account rather than by borrowing reserves or manipulating the capital account.